Farmakološki učinki česnovih pripravkov in njihove interakcije z zdravilnimi učinkovinami - Berginc, Katja (Farmacevtski vestnik, 2010)
The consumption of commercially available garlic supplements especially by chronic patients is continuously rising due to disease preventing effects, recognized in numerous preclinical and clinical studies. However, combining inconventional therapy utilized drugs with garlic phytochemicals can lead to serious pharmacokinetic and pharmacodynamic interactions. Namely, in some cases significant plasma profile changes of applied drugs and their metabolites, caused by intestinal and hepatic CYP inhibition and/or altered efflux membrane transporter activity, have been recognized in the presence of garlic phytochemicals leading to therapeutic failure or toxic side effects. There are also reports on pharmacodynamic interactions between drugs with narrow therapeutic window (i.e. warfarin) and garlic. Therefore combining garlic supplements and certain drugs should be closely monitored or in some cases even discontinued.
Keywords: citokromi; česen; farmacevtski preparati; interakcije